2017
DOI: 10.3151/jact.15.278
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Apparent Electrical Resistivity Measured by Four-Probe Method with Water Content Distribution in Concrete

Abstract: The electrical resistivity of concrete is an important value for designing electrochemical anti-corrosive methods or a durability indicator of reinforced concrete structures. It is well known that the four-probe method (the Wenner method) can be useful one for non-destructive evaluation of electrical resistivity. However, it has been pointed out that the measured results must be identified as an apparent value including the effect of water content gradient in concrete. In order to consider the engineering prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The four-probe method is usually used to measure the surface resistances of cylindrical or prismatic specimens [4,5,15,19]. In this method, as shown in Fig.…”
Section: Four-probe or Wenner Probe Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The four-probe method is usually used to measure the surface resistances of cylindrical or prismatic specimens [4,5,15,19]. In this method, as shown in Fig.…”
Section: Four-probe or Wenner Probe Methodsmentioning
confidence: 99%
“…In the four-point method, a four-probe device is placed on the surface of the concrete specimen, a voltage difference is applied between the two medium probes and the amount of current between the two external probes is measured and the resistance (R) is obtained by using the Ohm law. The resistivity of the specimen is obtained by multiplication of coefficient 2 a [15,16,19]. Here, a is the distance between the probes.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of temperature was studied by Coyle et al (2016) who reported that ρ is reduced by factor of 3 when the temperature increases from 5 to 30°C. The strong effect of moisture and moisture gradients on ρ was thoroughly investigated by Minagawa et al (2017), whilst the role of reinforcement on ρ was dealt with by Angst and Elsener (2014) and by Salehi et al (2016). Improving the conditions for site measurement of the electrical resistivity ρ as, for instance, by trying to saturate the concrete surface, is far from easy Presuel-Moreno et al (2010).…”
Section: Relation In Situ Tests Vs Strengthmentioning
confidence: 99%
“…Nevertheless, the four-probe method is the most common method used in large-scale soil electivity surveys due to its high accuracy [20]. It should be noted that the apparent resistivity measurement by the four-probe method was based on the assumption that object medium was homogeneous [30].…”
Section: In Situ Detection Of Clogging In a Lab-scale Hssf Cwmentioning
confidence: 99%